Effect of pyrolysis process parameters on electrical, physical, chemical and electro-chemical properties of SU-8-derived carbon structures fabricated using the C-MEMS process. (2018) - Pramanick, Bidhan; Vazquez-Pinon, Matias; Torres-Castro, Alejandro; Martinez-Chapaa, Sergio O.; Madou, Marc
Abstract: Pyrolysis is the process to thermally decompose an organic material into its carbon backbone in an oxygen-free environment. This process is used in the Carbon-MEMS fabrication technology to carbonize micro-structures patterned on a substrate. The properties of the resulting carbon material are dependent on either the carbon precursor or the pyrolysis conditions. In this work, SU-8 photoresist was used as the carbon precursor to study the effects of three pyrolysis parameters: 1) maximum pyrolysis temperature (600°C, 700°C, 800°C, and 900°C), 2) temperature ramp rate (2.5°C/min, 5°C/min, 10°C/min, and 20°C/min), and 3) nitrogen flow rate (3l/min, 4.5l/min, 6l/min, and 7.5l/min). To studythe effect of the maximum temperature, the temperature ramp rate and nitrogen flow rate were kept constant to 5°C/min and 6l/min respectively. For the temperature ramp rate experiments, we kept the maximum pyrolysis temperature and nitrogen flow rate constant to 900°C and 6l/min respectively. For the nitrogen flow rate study, the maximum pyrolysis temperature and temperature ramp rate were kept constant to 900°C and 5°C/min respectively. We found that no polymer structures persisted under the following conditions: 900°C maximum pyrolysis temperature, 5°C/min temperature ramp rate, and 3l/min nitrogen flow rate. Under these conditions the nitrogen flow rate is not high enough to keep the furnace environment (approximate volume of the furnace tube we used is 6l) entirely inert; in the pyrolysis process, even a small amount of oxygen destroys the intended C-MEMS. All the carbon samples were characterized using 4-point probe measurement for electrical resistivity; confocal microscopy for pore size determination; Raman spectroscopy, electron diffraction x-ray spectroscopy (EDX), and x-ray photoelectron spectroscopy (XPS) for chemical characterization. Furthermore, the samples were electrochemically characterized using cyclic voltammetry in a 1mM K4Fe(CN)6 and 0.5M KCl solution. The characterization results suggest that samples prepared under the following conditions - 900°C maximum pyrolysis temperature, 5°C/min temperature ramp rate, and 6l/min nitrogen flow rate, exhibit the best electrical, physical, chemical and electrochemical properties among the other conditions used.